The Influence of Parents' Understanding of it in Supervising Early Childhood Learning - Trijiarni Trijiarni; Sri Haryanto; Sofan Rizqi (Generasi Sains Indonesia, 2026)
This study aims to examine how parents’ understanding of information technology influences the supervision and support of early childhood learning in a technology-mediated environment. A qualitative research design was employed, involving parents and teachers in an early childhood education institution. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using an interactive thematic approach. The findings reveal that parents’ understanding of digital technology is largely experiential and varies in depth, affecting their ability to supervise and support children’s learning effectively. Active mediation, characterized by parental involvement and interaction during technology use, was found to be more effective than passive or restrictive approaches. In addition, teachers play a critical role as mediators by guiding both children and parents, facilitating alignment between school and home learning environments. The novelty of this study lies in its conceptualization of parental digital literacy as an enacted and relational process shaped by interaction and context. The study highlights the importance of collaborative supervision and structured guidance in maximizing the educational value of digital technology. These findings provide implications for developing integrated digital literacy programs that strengthen parent–teacher collaboration and promote developmentally appropriate technology use in early childhood education.